Corvids congregate to breeding colonies of a burrow‐nesting seabird. (18th September 2015) - Ekanayake, Kasun B.; Weston, Michael A.; Dann, Peter; Sutherland, Duncan R.
Abstract: Egg predation is a major cause of reproductive failure among birds, and can compromise the viability of affected populations. Some egg predators aggregate near colonially breeding birds to exploit the seasonal increase of prey resources. We investigated spatial and temporal variations in the abundance of an egg predator (little raven C orvus mellori ; Corvidae) to identify whether ravens aggregate spatially or temporally to coincide with any of three potential prey species: burrow‐nesting little penguin ( E udyptula minor ; Spheniscidae), short‐tailed shearwater ( A rdenna tenuirostris ; Procellariidae), and surface‐nesting silver gull ( C hroicocephalus novaehollandiae ; Laridae). We derived spatially explicit density estimates of little ravens using distance sampling along line transects throughout a calendar year, which encompassed little penguin, short‐tailed shearwater and silver gull breeding and non‐breeding seasons. High raven abundance coincided temporally with penguin and gull egg laying periods but not with that of shearwaters. The spatial distribution of raven density corresponded with the little penguin colony but not with shearwater or gull colonies. Thus, the presence of little penguin eggs in burrows correlated strongly with little raven activity, and this implies that little ravens may have learnt to exploit the plentiful subsurface food resource of little penguin eggs. Corvid management may be required to maintain the viability of this socially and economically important penguin colony.